ANALISIS KEMISKINAN RUMAH TANGGA DI KECAMATAN DUMBO RAYA KOTA GORONTALO - Nur Eng Mokodompit; Umar Sako Baderan; Ynati Yanti (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This study aims to identify the poverty of poor households in Dumbo Raya District, Gorontalo City and to examine and analyze the causes of Household Poverty in Dumbo Raya District, Gorontalo City. This study uses a quantitative approach. Sources of data obtained from a questionnaire with 56 respondents. The analytical tool used is multiple linear regression with the help of SPSS in its analysis. The results showed that the number of poor people in Dumbo Raya District was 563 people. Based on the results of the analysis, it turns out that the number of poor people is not able to meet 3 (three) basic needs, namely food, clothing, and housing very little, and more are unable to meet the three basic needs. The results of calculations using multiple regression turned out to be known that the poverty that occurred greatly affected the fulfillment of the three basic needs, as indicated by the R Square correlation relationship of only 5.8 percent. This means that the ability of the poor to meet their basic needs, namely food, clothing and housing, is only 5.8 percent while the remaining 94.2 percent are really poor and unable to meet the three basic needs.